Early Focal Segmental Glomerulosclerosis as a Cause of Renal Allograft Primary Nonfunction. (23rd May 2013) - Griffin, Emma J.; Thomson, Peter C.; Kipgen, David; Clancy, Marc; Daly, Conal
Abstract : Background. Primary focal segmental glomerulosclerosis (FSGS) is one of the commonest causes of glomerular disease and if left untreated will often progress to established renal failure. In many cases the best treatment option is renal transplantation; however primary FSGS may rapidly recur in renal allografts and may contribute to delayed graft function. We present a case of primary nonfunction in a renal allograft due to biopsy-proven FSGS. Case Report. A 32-year-old man presented with serum albumin of 22 g/L, proteinuria quantified at 12 g/L, and marked peripheral oedema. Renal biopsy demonstrated tip-variant FSGS. Despite treatment, the patient developed progressive renal dysfunction and was commenced on haemodialysis. Cadaveric renal transplantation was undertaken; however this was complicated by primary nonfunction. Renal biopsies failed to demonstrate evidence of acute rejection but did demonstrate clear evidence of FSGS. The patient was treated to no avail. Discussion. Primary renal allograft nonfunction following transplantation is often due to acute kidney injury or acute rejection. Recurrent FSGS is recognised as a phenomenon that drives allograft dysfunction but is not traditionally associated with primary nonfunction. This case highlights FSGS as a potentially aggressive process that, once active in the allograft, may prove refractory to targeted treatment. Preemptive therapies in patients deemed to be at high risk of recurrent disease may be appropriate and should be considered.